Survival of the fittest, or of the fastest? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Regulations affecting the media have been liberalised to a large extent in many countries, and are expected to become so in more hesitant countries. This offers opportunities for more diversity of information, but only as far as finance and funds...